Investigation of functionals of neutron flux influencing onto VVER-440 reactor pressure vessel - S. M. Pugach; O. V. Grytsenko; V. L. Diemokhin; V. N. Bukanov (Âderna Fìzika ta Energetika, 2008)
The calculational procedure for determination of irradiation conditions of VVER-440 reactor internals is presented. Using the developed procedure, irradiation conditions of Rovno NPP Unit1&2 VVER-440 reactor internals – baffle, basket and barrel – are determined. Distributions of neutron flux functionals at surfaces of these internals at both reactors are analyzed for different core arrangements.